Carpal tunnel syndrome severity, hand discomfort, and usability among three types of computer mouse. - Oveisi, Elahe; Khanlari, Payam; Ebrahimzadeh-Afrouzi, Mahdi (Work, 2024)
BACKGROUND: Numerous people use computer mice for long hours, especially in offices. Mouse users reported various pains and discomfort. OBJECTIVE: The study aimed to assess three types of most common mice (vertical, traditional, flat) in Iran in terms of their effects on carpal tunnel syndrome, hand discomfort, and usability. METHODS: The Boston Carpal Tunnel Syndrome questionnaire, the Cornell Hand Discomfort Questionnaire (CHDQ), System Usability Scale (SUS), and Workplace Ergonomic Risk Assessment (WERA) scores were used to assess vertical, traditional, and flat mice. In addition, the participant's hand position was analyzed by observation method. RESULTS: Most participants had medium carpal tunnel syndrome severity; however, flat mouse users had a higher score, and the difference between mice was insignificant (p > 0.05). Most mouse users felt discomfort in their small and ring fingers, and the type of mouse significantly affected thumb discomfort level. More flat users felt Pain in the different parts of their hands. The flat mouse has the least SUS score. There was a significant difference between the three mice regarding SUS scores (p < 0.05). WERA mean values were acceptable for numerous mice. Adopting neutral wrist postures was more common among vertical, flat, and traditional mouse users, respectively; however, the flat mouse users tended to bend their fingers. CONCLUSION: There are differences between vertical and traditional flat mice in terms of ergonomic indicators. Although more studies are needed, it seems that vertical mice are better in some indicators.